Blood Groups More than Inheritance of Antigenic Substances - Fatima Shad, Kaneez (IntechOpen, 2022)
Every cell in our body including red blood cells is covered with special markers called antigens, a substance that triggers the immune system response. Millions of antigens are present on the membrane of red blood cells and are ignored by the immune system because they are self-antigens. However, if a person receives a transfusion of blood that contains different antigens from their own blood, there will be a severe and immediate attack by the cells of the immune system. Therefore, it is important to use the patient's same blood group for the transfusion. The blood group antigens not only perform a critical role in the function of cells but can also be used by viruses to gain access into the cells. This book includes nine chapters on different blood group antigens and their activities behind the scenes. Chapters address blood antigens and their association with cardiovascular diseases, thromboembolic diseases, malaria, and many other diseases and infections.